2019
DOI: 10.1002/fes3.186
|View full text |Cite
|
Sign up to set email alerts
|

Is the yield change due to warming affected by photoperiod sensitivity? Effects of the soybean E4 locus

Abstract: Modeling studies predict that global warming will shorten growth duration and reduce seed yield of early‐maturing soybean (Glycine max) cultivars, but that late‐maturing cultivars could mitigate this reduction. This is widely discussed but has not been validated experimentally. Time of soybean maturation is determined by several photoperiod‐sensitive loci. Here, we focused on the E4 locus, and tested the hypothesis that this locus would mitigate the growth period shortening and yield reduction due to warming. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…36 Changing to a variety with higher heat time requirements (thus prolonging the growth period) can therefore stabilize soybean yield. 37 Similar countermeasures have been reported for maize in the corn belt of the USA, 38 winter wheat in China, 13 and cotton on the North China Plain. 39 Numerous previous studies based on statistical or crop modeling have reported negative impacts of global warming on crop yields.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…36 Changing to a variety with higher heat time requirements (thus prolonging the growth period) can therefore stabilize soybean yield. 37 Similar countermeasures have been reported for maize in the corn belt of the USA, 38 winter wheat in China, 13 and cotton on the North China Plain. 39 Numerous previous studies based on statistical or crop modeling have reported negative impacts of global warming on crop yields.…”
Section: Discussionsupporting
confidence: 55%
“…Increasing temperatures accelerate soybean growth and shorten the vegetative and reproductive growth stages, 34 a simulation study found that a reduction in soybean filling days of nearly 8% due to warming 36 . Changing to a variety with higher heat time requirements (thus prolonging the growth period) can therefore stabilize soybean yield 37 . Similar countermeasures have been reported for maize in the corn belt of the USA, 38 winter wheat in China, 13 and cotton on the North China Plain 39 .…”
Section: Discussionmentioning
confidence: 74%
“…The partial correlation coefficient between mean temperature and seeds per pod with a fixed mean FASW during the 20 days after R5 was 0.864 (p < 0.001). Although the number of seeds per pod remains stable under a wide range of temperatures [32], Kurosaki and Yumoto [33] report that low temperature (15.5 • C mean temperature) for four weeks in the flowering season reduced the number of seeds per pod in soybean cultivars in Hokkaido (the northernmost prefecture in Japan). In this study, the mean temperature was 22.6 • C during the period from R2 to R5 and 19.3 • C for the 20 days after R5 in the late-sown soybeans.…”
Section: Seed Yield Number Of Nodesmentioning
confidence: 99%
“…Increasing temperature can accelerate the growth cycle, leading to earlier senescence, and decrease both canopy radiation capture and biomass [42]. Kumagai et al (2020) [43] also found crop phenological stages responded differently to increasing temperature; specifically, increased temperature shortened the period from emergence to flowering and grain filling to maturity but prolonged the period during heading and flowering. Our study found the actual lengths during heading and flowering had an increasing trend at 0.11 day•yr −1 , 0.38 day•yr −1 and 0.20 day•yr −1 in NEP, YNP and SMLYR, respectively (Table 3), which indicated that increasing temperature has shortened the period before heading or after flowering.…”
Section: Spatial and Temporal Variations Of Cold Stressmentioning
confidence: 99%